A new genus of tribe Dikraneurini (Hemiptera: Cicadellidae: Typhlocybinae) from China based on a new species and genus checklist from China provided - Jiao, Meng; Yang, Maofa; Yan, Bin; Yu, Xiaofei (Zootaxa, 2024)
A new leafhopper genus Sugea gen. nov. is described and illustrated here based on type species Sugea obtusangula sp. nov. from Yunnan Province, China, and placed in the tribe Dikraneurini (subfamily Typhlocybinae). Sugea is easily distinguishable from all other known dikraneurine genera based on the angulate face profile with a distinct submarginal furrow present along the anterior and lateral margins.